2005
DOI: 10.1897/04-483r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental pollution on microsatellite DNA diversity in wood mouse (Apodemus sylvaticus) populations

Abstract: Ten microsatellite DNA loci were surveyed to investigate the effects of heavy metal pollution on the genetic diversity and population genetic structure of seven wood mouse (Apodemus sylvaticus) populations along a heavy metal pollution gradient away from a nonferrous smelter in the south of Antwerp (Flanders, Belgium). Analysis of soil heavy metal concentrations showed that soil Ag, As, Cd, Cu, and Pb decreased with increasing distance from the smelter. Genetic analyses revealed high levels of genetic variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 62 publications
4
25
0
Order By: Relevance
“…This could indicate that metal contamination acted as a directional selective pressure to change gene frequencies in the exposed population (site I) relative to the references, but this change in frequencies was not reflected by a loss of genetic diversity. These results are in agreement with some of the mentioned studies, which also found that the genetic differentiation between populations of fish (McMillan et al, 2006;Mulvey et al, 2002Mulvey et al, , 2003Roark et al, 2005) and wood-mouse (Berckmoes et al, 2005) was more correlated with environmental contamination than with geographical distance and that these changes reflected selection by contaminants (Ownby et al, 2002).…”
Section: Population Genetic Differentiationsupporting
confidence: 93%
See 1 more Smart Citation
“…This could indicate that metal contamination acted as a directional selective pressure to change gene frequencies in the exposed population (site I) relative to the references, but this change in frequencies was not reflected by a loss of genetic diversity. These results are in agreement with some of the mentioned studies, which also found that the genetic differentiation between populations of fish (McMillan et al, 2006;Mulvey et al, 2002Mulvey et al, , 2003Roark et al, 2005) and wood-mouse (Berckmoes et al, 2005) was more correlated with environmental contamination than with geographical distance and that these changes reflected selection by contaminants (Ownby et al, 2002).…”
Section: Population Genetic Differentiationsupporting
confidence: 93%
“…Even though the reduction of genetic diversity in populations inhabiting contaminated areas has been reported in several aquatic and terrestrial species (Belfiore and Anderson, 2001;Bickham et al, 2000), recent studies employing either modern molecular methodologies, such as AFLP analysis (McMillan et al, 2006), microsatellite analysis (Berckmoes et al, 2005) and mitochondrial gene sequencing (Mulvey et al, 2003), or more classical methods, especially allozyme analysis Roark et al, 2005) have found little or no evidence for this effect. Nevertheless, this possible effect is one of the major concerns of modern conservation biology and ecotoxicology (Bagley et al, 2002;van Straalen and Timmermans, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The probability of DNA damage being converted into a permanent and/or heritable sequence alteration depends on the type of damage, the repair pathway recruited, the rate of repair and the fidelity and completeness of repair (Preston & Hoffman 2001). In some instances, mutagenic chemicals have been shown to increase genetic variation (albeit at neutral markers) (Chen et al 2003;Berckmoes et al 2005;Eeva et al 2006), but in other cases, to reduce it. This reduction can have negative impacts on wildlife by increasing the frequency of deleterious mutations that are selected against, causing bottlenecks, impairing gene flow (reviewed in Van Straalen & Timmermans 2002) and, less dramatically, lead to cumulative erosion of reproductive fitness (reviewed in Bickham et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, an increase in genetic diversity levels in 36.4% of the analyzed species was found, like Lumbricus rubellus: Cd, Zn, Cu, Pb [49]; Cepaea nemoralis: Cd, Cr, Cu, Ni, Pb, Zn [50]; Parus major: Cd, Zn, Cu, Pb, Ni, Al, As, Cr, Sn [48] and Larus argentatus (steel), [51]. Meanwhile, the remaining 18.2% of the studied species did not register changes in genetic diversity levels, such as: Apodemos sylvaticus: Cd, Zn, Cu, Pb, Ni, Al, Ag, As, Co, Mn, Fe [42] and Succinea putris: Cd, Cr, Cu, Ni, Pb, Zn [50].…”
Section: Heavy Metal Effects On Genetic Diversity Of Exposed Populationsmentioning
confidence: 99%
“…In both cases, these responses are the consequence of the adaptation of the population to polluted environments [3,[41][42][43][44].…”
Section: Heavy Metal Effects On Genetic Diversity Of Exposed Populationsmentioning
confidence: 99%